Thyroid transcription factor-1 expression in rectal adenocarcinoma metastatic to the lung. (2023) - Takanashi, Yusuke; Kurachi, Kiyotaka; Fujihiro, Mayu; Sekihara, Keigo; Torii, Kakeru; Kawase, Akikazu; Matsubayashi, Yuta; Hayakawa, Takamitsu; Baba, Satoshi; Sugimura, Haruhiko; Iwashita, Toshihide; Funai, Kazuhito
Abstract: Distinguishing metastatic lung tumors from primary lung cancer is essential for planning the appropriate treatment strategy. Thyroid transcription factor-1 (TTF-1) is a reliable immunohistochemistry (IHC) marker for differentiating between primary lung adenocarcinomas and metastatic lung tumors originating from colorectal adenocarcinomas. Herein, we report a rare case of TTF-1 expression in both the metastatic lung tumor and primary rectal adenocarcinoma. Aside from the similar histological characteristics of both tumors when stained with hematoxylin–eosin, the IHC patterns, including negative results for alveolar epithelium markers (napsin A and CK7) and positive results for intestinal markers (CK20, CDX2, SATB2, and β-catenin), of the lung tumor and the primary rectal adenocarcinoma strongly supported the final diagnosis. Considering the non-negligible frequency of TTF-1 positivity in colorectal adenocarcinomas, applying the IHC panel including multiple markers for alveolar epithelium and intestinal differentiation, would be helpful to support the diagnosis of metastatic lung tumor from a rectal adenocarcinoma. Highlights: TTF-1 expression in tumors originating from organs other than the lung and the thyroid is rare. We report a rare case of TTF-1 expression in rectal adenocarcinoma metastatic to the lung. The consistent positivity of TTF-1 and intestinal markers between the lung and rectal tumor supported the diagnosis.